Gis-aided accessibility assessment for community park planning: Youth-friendly neighborhood parks in Subang Jaya, Malaysia - Zainol, R.; Wang, C.; Wood, L.C.; Zulkia, D.R.; Nellis, S. (Locke Science Publishers, 2017)
More sedentary modern lifestyles reflect the reduction in physical activities conducted in recreational areas, which has a negative effect on youth health. To reduce the incidence of obesity resulting from modern urban lifestyles, providing public open spaces close to residential areas should be considered. This study aimed to assess the accessibility of youth-friendly neighborhood parks in UEP Subang Jaya (USJ), Malaysia. Aided by geographic information system (GIS) techniques, Moran's I and local indicators of spatial association (LISA), the analysis showed that the density of the existing neighborhood parks is sufficient to accommodate the needs of the local youth population in USJ. However, the analysis demonstrated that the presence of gated communities has an important impact on neighborhood park planning. Even in sections that have neighborhood parks, the parks are not always easily accessible to the youth due to their poorly planned locations. The GIS techniques and spatial statistical analysis used in this study can improve the placement of neighborhood parks to ensure that they will be sufficiently accessible. The use of these GIS techniques is recommended for relevant agencies, especially local authorities, municipal councils, and town planning divisions, for the development of neighborhood parks in the future.